CHARACTERISTICS OF EPIRETINAL MEMBRANE REMNANT EDGE BY OPTICAL COHERENCE TOMOGRAPHY AFTER PARS PLANA VITRECTOMY. Issue 11 (November 2017) - Gaber, Raouf; You, Qi Sheng; Muftuoglu, Ilkay Kilic; Alam, Mostafa; Tsai, Frank F.; Mendoza, Nadia; Freeman, William R.
Abstract : Purpose: To evaluate the incidence, characteristics, and the progression of epiretinal membrane (ERM) remnant edge seen by optical coherence tomography after ERM peeling. Methods: A retrospective chart review was conducted for 86 eyes of 85 consecutive patients who were diagnosed with ERM and underwent pars plana vitrectomy for epiretinal membrane peeling between 2013 and 2014. Data collected and analyzed included age, gender, preoperative and postoperative visual acuity, use of indocyanine green dye to stain internal limiting membrane, tamponade used after vitrectomy, ERM edge boundaries, presence of cystoid macular edema, and central foveal thickness. Results: An ERM remnant edge was detected in 33/86 study eyes (38.4%) at the first postoperative optical coherence tomography scan. Compared with those without an ERM remnant, patients with an ERM remnant after surgery were significantly older at baseline and had a higher incidence of ERM recurrence at their last visit. They were not significantly different in terms of gender, preoperative and postoperative visual acuity, reduction of central foveal thickness from baseline, proportion of eyes with preoperative ERM elevation on optical coherence tomography, presence of macular edema before surgery, intraoperative use of indocyanine green staining for ILM peeling, or tamponade used. Based on the edge morphology, we classified the ERM remnant into three types: Type 1 was flat and blended with the retina (14/33 eyes, 42.4%), Type 2 was flat but stepped (17/33 eyes, 51.5%), and Type 3 was elevated (2/33 eyes, 6.0%). A significantly higher risk of ERM recurrence was seen in Type 2 and Type 3 ERM remnants (75% and 100%, respectively) than Type 1 ERM remnants (10%). Conclusion: An ERM remnant edge was detected by optical coherence tomography after ERM peeling in 38.4% of eyes. The presence of a postoperative ERM edge was associated with a higher risk of ERM recurrence, particularly in Type 2 and Type 3 ERM remnants. Abstract : An epiretinal membrane remnant edge was detected by optical coherence tomography after epiretinal membrane peeling in 38.4% of eyes and was associated with a higher risk of epiretinal membrane recurrence, particularly when the edge is flat and stepped or elevated.